Kecerdasan Emosional Anak Era Society 5.0 Melalui Prinsip-Prinsip Komunikasi Keluarga Dalam Amsal 15:1, 4 - Patrick Byonjovi Lazarus; Farel Yosua Sualang (Sabda: Jurnal Teologi Kristen, 2026)
Abstract:The family is the first and foremost institution in shaping a child’s character. In the complexity of the Society 5.0 era, which is marked by technological disruption and changing patterns of social interaction, family communication plays a vital role in both emotional intelligence and character formation of children. To date, there has been a gap in interpretation between Manase Gulo and Armen Oganessian, who, in discussing Proverbs 15:1 and 4, focus only on communication strategies for preventing or resolving conflict, particularly in building household harmony through the use of words that can either edify or destroy. This study aims to provide parents with foundational values as a guide for good communication, thereby positively impacting children’s emotional intelligence and character development. Employing a qualitative method with a hermeneutic approach to wisdom literature and literature synthesis, this article identifies three communication principles parents can apply in interacting with their children: first, gentleness, as soft words provide a concrete model for children in managing emotions; second, the use of constructive speech, which influences the development of children’s ethics and spirituality; and third, avoiding hurtful words, which can serve as a foundation for emotional regulation and character building. These findings offer practical input for parents to engage in communication based on biblical principles so that children may grow to be emotionally intelligent and of good character.Abstrak:Keluarga merupakan institusi pertama dan utama dalam membentuk karakter anak. Di tengah kompleksitas era Society 5.0 yang ditandai oleh disrupsi teknologi dan perubahan pola interaksi sosial maka komunikasi dalam keluarga memainkan peran vital dalam kecerdasan emosional maupun pembentukan karakter anak. Sejauh ini terjadi kesenjangan interpretasi antara Manase Gulo dan Armen  Oganessian ketika membahas Amsal 15:1 dan 4 hanya menekankan strategi komunikasi untuk mencegah atau menyelesaikan konflik, khususnya dalam membangun keharmonisan rumah tangga melalui penggunaan kata-kata yang dapat membangun atau merusak. Penelitian ini bertujuan untuk memberikan rujukan kepada orangtua agar memiliki nilai dasar yang menjadi pedoman dalam berkomunikasi yang baik sehingga berdampak positif dalam kecerdasan emosional dan pembentukan karakter anak. Menggunakan metode studi kualitatif dengan pendekatan hermeneutik sastra hikmat dan sintesis literatur maka artikel ini menemukan tiga prinsip komunikasi yang dapat diterapkan orangtua dalam komunikasi dengan anak yakni : pertama memiliki kelembutan, perkataan yang lembut  memberi model nyata bagi anak tentang bagaimana mengelola emosi; kedua adalah menggunakan kalimat yang membangun, mempengaruhi pembentukan etika dan spiritualitas anak; ketiga menghindari kata yang melukai, dapat menjadi fondasi regulasi emosi dan karakter anak. Menjadi masukan bagi orangtua agar melakukan komunikasi sesuai prinsip alkitabiah agar anak cerdas secara emosi dan memiliki karakter yang baik.